1957
DOI: 10.1295/koron1944.14.101
|View full text |Cite
|
Sign up to set email alerts
|

Branched Structure of Polyvinyl Acetate

Abstract: For studying the branching of polyvinyl acetate(PVAc)and polyvinyl alcohol(PVA),the polymerization of vinyl trimethylacetate in the presence of PVAc was examined.The differences between PVAc and polyvinyl trimethylacetate (PVTMAc) are as follows:1 PVTMAc is thoroughly insoluble in 25 aqueous methanol.2.The rate of alkali-catalized saponification of PVTMAc is remarkably slower than that of PVAc.3.The infra-red absorption band at 12.49 tt for PVAc and the band at 13.05 it for PVTMAc are the key bands.From these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1972
1972
2005
2005

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…16 Murahashi, et al, have found that long branching on PV A does not affect the PV A-iodine reaction. 17 This result is reasonable, for the presence of long branching probably shows little effect with respect to the microstructure of PV A because of the small number of branching points per polymer molecule.…”
Section: Discussionmentioning
confidence: 99%
“…16 Murahashi, et al, have found that long branching on PV A does not affect the PV A-iodine reaction. 17 This result is reasonable, for the presence of long branching probably shows little effect with respect to the microstructure of PV A because of the small number of branching points per polymer molecule.…”
Section: Discussionmentioning
confidence: 99%
“…Investigation has shown that chain transfer to polymer occurs predominantly on the acetate methyl group in preference to the chain backbone; one estimate of the magnitude of the predominance is 40-fold (94,95). The number of branches per molecule of poly(vinyl acetate) polymerized at 60 • C is ca 3, at 80% conversion.…”
Section: Chain Transfermentioning
confidence: 99%